PERKEMBANGAN JAGUNG PADA DEKADE TERAKHIR SERTA PELUANG PENGEMBANGAN KEDEPAN - WAYAN SUDANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Maize is the one important cereal crop after rice, for the last decade domesticdemand for maize was steadily increasing. This study is aimed to evaluate thedevelopment of maize production for the last decade, and the opportunity ofmaize production development in future. Based on CBS data, during the lastdecade (1990 – 2000) there was a big opportunity to develop maize productionin the future, through intensification or extensification. Intensification, can bemet by minimize yield gap between farm’s yield and potential yield byintroducing of improve technology, and use of high yield variety. Extensificationcan be achieved by increasing cropping index through implementation propercropping pattern especially on irrigated land, and in the upland condition byimplementing intercropping technique. Extensification also can be done byutilizing swampy area and upland area, where are available in outer of Javaisland.